Uji Beda Dampak Pandemi Covid 19: Pengaruh Pertumbuhan Aset, Profitabilitas, dan Struktur Modal terhadap Nilai Perusahaan Sub Sektor Restoran, Hotel & Pariwisata - Syti Sarah Maesaroh; M Sandi Marta; Nugraha Nugraha; Maya Sari (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2020)
Value is one of the important indicators in a company. This study aims to determine the faktors that affect firm value and analyze the effect of the Covid-19 pandemic on firm value in the restaurant, hotel, and tourism sub-sectors. Data analysis used multiple regression analysis through a quantitative descriptive approach. The company sample consists of restaurant, hotel, and tourism sub-sector companies listed on the IDX in 2019 and 2020. The variables observed include aset growth, profitability, capital structure, and firm value. Hypothesis testing was conducted to determine the effect of the independent variable on the dependent variable. The different test of the impact of the Covid-19 pandemic is intended to compare conditions before the pandemic and during the pandemic. The results show that aset growth, profitability, and capital structure have a significant simultaneous effect on firm value. However, partially, aset growth shows a negative effect on firm value. The different test shows that the profitability, capital structure, and company value before the pandemic is significantly different when compared to during the pandemic. This indicates that the pandemic has had a huge impact on the company.